Sistem Hukum Perkawinan Pada Negara Hukum Berdasarkan Pancasila - Tengku Erwinsyahbana (Fakultas Hukum Universitas Riau, 2012)
Marriage is included as basic needs (rights) of everyhuman being, whose goal is to establish a family orhousehold who are happy and eternal by Belief in GodAlmighty. The inclusion of elements of the phrase “Be-lief in God Almighty” within the meaning of marriagementioned in Article 1 of Law no. 1 of 1974, indicatingthat the marriage can not be viewed simply as a mat-ter of personal (individual), but must also be viewedas the legal relationship between a man and a womanin a household that has religious values based on thePancasila as a life philosophy of the Indonesian na-tion.